New Orleans Carnival Balls : The Secret Side of Mardi Gras, 1870-1920 - Atkins, Jennifer (Book collections on Project MUSE., 2017)
As Jennifer Atkins suggests in New Orleans Carnival Balls, Mardi Gras has a secret side. After masking and parading through the streets, krewes retreat to theaters, convention centers, and banquet halls to spend the evening at lavish balls where krewe members could cultivate their sense of fraternity and celebrate their shared values. Atkins uses the concept of dance as a lens for examining Carnival, allowing her to delve deeper into the historical context and distinctive rituals of Mardi Gras in New Orleans. Dancing is a particularly illuminating social practice, and by using it to probe into old-line festivities, Atkins is able to decode the mysterious rituals that have mostly remained secret. Beyond presenting readers with a new means of thinking about Mardi Gras, Atkins s work situates dance as culturally and socially relevant to historical inquiry, contributing to our understanding of the usefulness of dance in examining the past.